2011
DOI: 10.1186/1471-230x-11-72
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Age in Predicting the Outcome of Caustic Ingestion in Adults: A Retrospective Analysis

Abstract: BackgroundAlthough the outcomes of caustic ingestion differ between children and adults, it is unclear whether such outcomes differ among adults as a function of their age. This retrospective study was performed to ascertain whether the clinical outcomes of caustic ingestion differ significantly between elderly and non-elderly adults.MethodsMedical records of patients hospitalized for caustic ingestion between June 1999 and July 2009 were reviewed retrospectively. Three hundred eighty nine patients between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
6
31
1
2
Order By: Relevance
“…We then used a multivariable Cox model to compare survival after adjustment on prognostic co-variates. We individually matched patients from the two groups (CT or no CT) on age (±2 years) [16,31], gender [16,32], and acid ingestion [6,16,33] then compared survival using a Cox model with a random effect on the pairs. All tests were two-sided at the 0.05 significance level.…”
Section: Discussionmentioning
confidence: 99%
“…We then used a multivariable Cox model to compare survival after adjustment on prognostic co-variates. We individually matched patients from the two groups (CT or no CT) on age (±2 years) [16,31], gender [16,32], and acid ingestion [6,16,33] then compared survival using a Cox model with a random effect on the pairs. All tests were two-sided at the 0.05 significance level.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike caustic ingestion in children, adults usually ingest strong corrosives with suicidal intent and lead to severe, life-threatening injuries with multiple long-term complications, including stricture, fistula formation and malignancy [7,15]. In the study, we found most caustic injury adults were also suicide intent with acid caustic agents (detergent or insecticides) at middle to older age in Taiwan.…”
Section: Discussionmentioning
confidence: 69%
“…At the end of the followup period, 1 patient (1%) in the esophagocoloplasty group and 17 patients (16%) in the colopharyngoplasty group had a tracheotomy tube (P < 0.0001). The median delay in jejunostomy removal was 3 [2][3][4][5] months after esophagocoloplasty and 9 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] months after colopharyngoplasty (P < 0.0001).…”
Section: Functional Outcomesmentioning
confidence: 99%